2017
DOI: 10.1111/fwb.12949
|View full text |Cite
|
Sign up to set email alerts
|

Whole‐landscape modelling of compositional turnover in aquatic invertebrates informs conservation gap analysis: An example from south‐western Australia

Abstract: Freshwater aquatic ecosystems are in decline due to intensifying land use, salinisation, water abstraction and climate change. Understanding compositional patterns in aquatic biota is a useful step towards better management of aquatic ecosystems. We used generalised dissimilarity modelling (GDM) to predict compositional turnover in riverine invertebrate fauna (primarily insects) as a function of environment. Conceptual understanding of major drivers of aquatic invertebrate species distribution helped decide wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 95 publications
0
6
0
Order By: Relevance
“…Recent predictions of warming of up to 3–4°C by 2090 (IPCC, 2014) mean that these trends will continue to accelerate until at least the end of the century. Few invertebrates appear on conservation listings in SWA (a common problem worldwide; Chichorro et al, 2019); however, recently some SWA stream fauna have been identified as candidates for conservation listing (Pennifold, 2018; Pennifold et al, 2017). But we contend that the numbers of SWA stream‐dwelling species under threat of range contraction and eventual extinction due to climate drying will be far greater than identified under current predictions because many, perhaps most, common species will be affected.…”
Section: Discussionmentioning
confidence: 99%
“…Recent predictions of warming of up to 3–4°C by 2090 (IPCC, 2014) mean that these trends will continue to accelerate until at least the end of the century. Few invertebrates appear on conservation listings in SWA (a common problem worldwide; Chichorro et al, 2019); however, recently some SWA stream fauna have been identified as candidates for conservation listing (Pennifold, 2018; Pennifold et al, 2017). But we contend that the numbers of SWA stream‐dwelling species under threat of range contraction and eventual extinction due to climate drying will be far greater than identified under current predictions because many, perhaps most, common species will be affected.…”
Section: Discussionmentioning
confidence: 99%
“…For example, finite budgets mean that the acquisition of incompletely surveyed land parcels to complement reserve systems must be prioritised. Indeed, much of the literature concerning spatial representation deals with conservation planning (Arponen et al., 2008; Ferrier, 2002; Pennifold et al., 2017; Williams et al., 2006), and, in particular, reserve selection (Araújo et al., 2001; Engelbrecht et al., 2016; Faith & Walker, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Output of the GDM model was used to predict compositional turnover across South Africa. The proportional representation of ecological environment (scaled using spider data) in conservation areas and the sample coverage of these environments by the database were quantified as a continuous fraction of the entirety of South Africa (Pennifold et al 2017). Lesotho and Swaziland were excluded from this analysis as layers for conserved areas in these countries were not available.…”
Section: Methodsmentioning
confidence: 99%